Desain Tempat Pembuangan Sampah Kawasan Pantai di Pantai Krakal, Gunungkidul - Ranivan, Imam Asri; Abdur Rasyid, Aban; Winda Setyaningsih, Afriana; Putri Rahayu, Anggita; Fatin Hasanah, Azizah; Nur Evita Sari, Dela; Safitri, Dian; setiawan, Feri; Asnan Alfaru, Irvansyah; Winarni, Isti; Sulistyaningrum, Laela; Renaldi Febriansyah, Muhammad; Ajeng Wulandari, Putri; Dwi Pamungkas, Revangga; Putro Pamungkas, Tri; Eko Bawono, Septiono; Patria, Rizaldi (Media Komunikasi Dunia Ilmu Sipil (MoDuluS), 2023)
This program aims to reduce the waste population in the Krakal Beach area. Because there are many piles of garbage and the beach ecosystem has begun to be disturbed which has resulted in polluted sea water, beach sand becomes dirty, and piles of garbage emit odors so that the air is also polluted. The sample from this activity program consisted of photos/images taken directly from Krakal Beach, surveys and interviews from the local community and the local Pokdarwis chairperson. The data obtained was processed using a quantitative survey method to calculate and calculate the volume of waste so that it can estimate the required size of Temporary Disposal Sites to be built to accommodate this waste. It is hoped that this program can have a positive impact on the Krakal Beach ecosystem and provide comfort for visitors for the cleanliness created.